Clinical follow-up analysis of multidisciplinary treatment of children with spinal muscular atrophy - Xia, Y (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2022)
Objective: To analyze the follow-up and clinical effect of multidisciplinary treatment on the children with spinal muscular atrophy (SMA). Methods: The clinical data including nutritional status, respiratory function, bone health and motor function of 45 children with SMA who received multidisciplinary management 1-year follow-up in the Children's Hospital, Zhejiang University School of Medicine from July 2019 to October 2021 were retrospectively collected. Comparisons before and after management were performed using paired-samples t-test or Wilcoxon rank-sum test, etc. Results: The age of 45 patients (25 boys and 20 girls) was 50.4 (33.6, 84.0) months at the enrollment, with 6 cases of type 1, 22 cases of type 2, and 17 cases of type 3 respectively. After the multidisciplinary management, the cases of SMA patients with malnutrition decreased from 22 to 12 (P=0.030), the level of vitamin D were significantly increased ((45±17) vs. (48±14) nmol/L, t=-4.13, P<0.001). There was no significant difference in the forced vital capacity %pred, the forced expiratory volume at 1 second %pred, and the peak expiratory flow %pred ((76±19)% and (76±21)%, (81±18)% and (79±18)%, (81±21)% and (78±17)%; t=-0.24, 1.36, 1.21; all P>0.05). The Cobbs angle of scoliosis also improved significantly (8.0°(0°, 13.0°) vs. 10.0°(0°, 18.5°), Z=-3.01, P=0.003). The Hammersmith functional motor scale expanded scores of children with SMA type 2 and type 3 both showed significant elevation (11.0 (8.0, 18.0) vs. 11.0 (5.0, 18.5) scores, 44.0 (36.5, 53.0) vs. 44.0 (34.0, 51.5) scores, Z=2.44, 3.11, P=0.015, 0.002). Conclusion: Multidisciplinary management is beneficial for delaying the progression of the multi-system impairments of SMA patients, such as malnutrition, restrictive ventilation dysfunction and scoliosis